Open-Cellular Alumina Foams with Hierarchical Strut Porosity by Ice Templating: A Thickening Agent Study - Dammler, Kathleen; Schelm, Katja; Betke, Ulf; Fey, Tobias; Scheffler, Michael (Materials, 2021)
Alumina replica foams were manufactured by the Schwartzwalder sponge replication technique and were provided with an additional strut porosity by a freeze-drying/ice-templating step prior to thermal processing. A variety of thickeners in combination with different alumina solid loads in the dispersion used for polyurethane foam template coating were studied. An additional strut porosity as generated by freeze-drying was found to be in the order of similar to 20%, and the spacings between the strut pores generated by ice-templating were in the range between 20 mu m and 32 mu m. In spite of the lamellar strut pore structure and a total porosity exceeding 90%, the compressive strength was found to be up to 1.3 MPa. Combining the replica process with freeze-drying proves to be a suitable method to enhance foams with respect to their surface area accessible for active coatings while preserving the advantageous flow properties of the cellular structure. A two-to-threefold object surface-to-object volume ratio of 55 to 77 mm(-1) was achieved for samples with 30 vol% solid load compared to 26 mm(-1) for non-freeze-dried samples. The freeze-drying technique allows the control of the proportion and properties of the introduced pores in an uncomplicated and predictable way by adjusting the process parameters. Nevertheless, the present article demonstrates that a suitable thickener in the dispersion used for the Schwartzwalder process is inevitable to obtain ceramic foams with sufficient mechanical strength due to the necessarily increased water content of the ceramic dispersion used for foam manufacturing.
CRIS-Team WoS Importer:2021-04-02